The Devil Lake pothole (Ontario): Evidence of subglacial fluvial processes / La marmite de Devil Lake (Ontario) : une forme témoignant d’un processus fluviatile sous-glaciaire - Gilbert, Robert (Géographie physique et Quaternaire, 2000)
AbstractA pothole 1.93 m deep and 1.3 m maximum diameter is located near the crest of a ridge that forms one arm of an eroded anticline in para-gneiss of the Precambrian Shield in southeastern Ontario. It's position on high ground in a region of more than 100 m relief on the bed rock precludes its formation by modern subaerial stream flow or by streams that could have come from the retreating late Pleistocene glacier. The regional bedrock topography determined from topographic maps and a subbottom acoustic survey of nearby lakes exhibits a pattern of large-scale subglacial fluvial erosion reported for other sites in the region. The pothole formed in subglacial flow where discharge was concentrated along the limb of the anticline. As flow streamed around a small rock knob, a vortex was established at a fracture in the rock surface and initiated the erosion of the pothole. This configuration insured that subsequent flows were similarly focused. The occurrence of this pothole is further evidence of the importance of subglacial water as an agent of erosion and the shaping of landscape beneath the Laurentide Ice Sheet.